Tax revenue in ASEAN: Impact factors and policy recommendations - Men Thi Bui; Hang Thi Ngo; Giang Thi Cam Nguyen; Ha Ngan Duong (Global Business & Finance Review (GBFR), 2024)
Purpose: The paper aims to identify the factors that impact the budget revenues of countries in ASEAN economies. Design/methodology/approach: The paper applies fixed effect and random effect models on a 25-year database of ASEAN economies from 1991 to 2020. Findings: The research reveals that various factors such as trade openness, industry structure, inflation, and tax payment time have a significant impact on tax collection. However, no linkages between tax revenue and foreign direct investment demand and education levels. Factors including industrial proportion (IND), inflation rate (INF), trade openness (IMP), time to pay tax (TIME), and Agricultural added value (AGR) together significantly and statistically affect the tax revenue (TAX). Of these, variables that have a positive relationship with TAX include AGR, IND and TIME while INF is negatively related to tax. Research limitations/implications: The data from 2021 onwards has not been analyzed due to a lack of necessary data, which could show the impact of the COVID-19 pandemic on production and business and its effect on tax revenue. Originality/value: After a comprehensive and thorough variable selection and research design tailored for ASEAN economies, other than estimates on IND, IMP, and INF which are significantly consistent with most of the precedent literature, our research has reached some interesting findings recorded in our new variable (TIME), AGR, and FDI.
Keywords: 650; Tax; Policy; Tax Revenue; Foreign direct investment; Panel data